IMPACT OF COVID-19 PANDEMIC ON THE LOCAL TAX (International Conference on Social and Islamic Studies, 2021)
The purpose of government is to proper the community by using fund from the people, one of which is local tax. Covid-19 not only affects health, but also affects local tax conditions. The study was conducted with the aim to analyze whether there are difference local tax before and after covid-19 pandemic. The sample used in this study is the period of 2019 and 2020 in the report on budget realization. There are 34 provincial government in Indonesia as sample. Data were analyzed using IBM SPSS 23.0. Hypothesis testing is performed using paired sample t-test. The result of this study indicates that there are difference in local tax at the time before and after Covid-19 pandemic. The current pandemic situation has a major impact on regional economy, including in the taxation sector. The impact of the Covid-19 pandemic with the decline in local tax revenues was due to the people being affected by being laid off and partial lockdown. How long this pandemic lasts and how much impact it will have on economic activity will determine the future of the regional tax sector in Indonesia.